Analisis Laporan Arus Kas Dalam Menilai Kinerja Pada PT Sariguna Primatirta Tbk (Cleo) - Fahrizal Kelvin Prasetyo; Luqman Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This study for determining the impact of covid-19 pandemic on the performance of PT Sariguna Primatirta. The method used was descriptive method with the aim for describing the performance of financial statements of PT Sariguna Primatirta. The data was collected through secondary data in the form of Company Financial Statement Information from three periods starting from 2018 to 2020. Data collection's techniques used documentation techniques on the balance sheet and income statement of the company. The analysis method used was descriptive data analysis with financial ratio formulation and then delivered back with more informative and easy to understand. The analysis's results said that the company's financial statements showed that PT Sariguna Primatirta's financial performance experienced a less stable performance. Looking through the results of operating cash flows to current liabilities that do not show a significant increase. In 2019 showed the lowest ratio results compared to other years, except for the capital expenditure ratio showed the maximum results.